2019
DOI: 10.1016/j.sapharm.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of reflective practice in healthcare professions: Next steps for pharmacy education and practice

Abstract: Reflective practice strategies can enable healthcare practitioners to draw on previous experiences to render more effective judgment in clinical situations. The central argument presented in this commentary is that education programs and structures for continuing professional development (CPD) and revalidation of professionals sharpen their focus regarding self-assessment to identify gaps in skills and attitudes rather than merely as a means of on-going monitoring. Pharmacy undergraduate and professional educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…In their mixed-methods exploration of an art-therapy based group intervention for healthcare professionals, they found that viewing art developed relational connection in the group and making art connected individuals to their true emotions. Mantzourani et al's (2019) review of literature on reflective practices within healthcare professions adds an additional dimension to the function of reflective practice in professional development. Identifying personal strengths and limitations is an essential part of improving practice and thus of improving patient care; effective reflective practice strengthens self-awareness (Schon, 1983;Thompson & Pascal, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In their mixed-methods exploration of an art-therapy based group intervention for healthcare professionals, they found that viewing art developed relational connection in the group and making art connected individuals to their true emotions. Mantzourani et al's (2019) review of literature on reflective practices within healthcare professions adds an additional dimension to the function of reflective practice in professional development. Identifying personal strengths and limitations is an essential part of improving practice and thus of improving patient care; effective reflective practice strengthens self-awareness (Schon, 1983;Thompson & Pascal, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…18 This reflective practice is essential to support them to stimulate thought processes and achieve personal growth, in both educational and healthcare settings, and hence empower mentees to achieve best practice. 19 Van Ast created a mentee checklist to "manage up" for productive mentoring relationships. 20 These include identify your values, clarify your work ethic, identify knowledge and skills gaps, be warm to any assigned mentor and seek additional mentors, be open about the type of mentor you seek, agree on structure and terms of the relationship, ask questions, actively listen, follow through on assigned tasks, be committed to a meeting schedule, and discuss when the mentoring relationship should end.…”
Section: Menteesmentioning
confidence: 99%
“…2 These concepts require rigorous approaches, critical appraisal skills, and self-reflective practices to be applied to patient care. 4,5 Despite these evolving principles, there is a gap between the education of healthcare professionals and the application of these concepts.…”
Section: Introductionmentioning
confidence: 99%